Nebulization Therapy in Pediatric Patients with Bronchiolitis: A Literature Review - Kawilarang, Melani; Santoso, Tiffanie Almas; Dharmansyah, Renald Patria; Angela, Angela; Ferdiaananda, Muhammad Rizky (Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Bronchiolitis is one of the most common causes of hospitalization in children under two years old. The main treatment for bronchiolitis is supportive therapy. Nebulization therapy in pediatric bronchiolitis is still being controversial in clinical practice and based on guideline recommendations. The purpose of this study is to determine and review the beneficial effects of saline and nebulized therapy in pediatric patients with bronchiolitis. Literature searches were obtained through reference sources from Google Scholar, PubMed, Proquest, JSTOR, ScienceDirect, and SAGE. Inclusion criteria were original articles, published in Indonesian and English, and assessed nebulization therapy's outcome in pediatric bronchiolitis patients. The treatment of administering nebulized saline NS or HS 3% can provide more effective results than treatment without nebulization. Many studies using nebulized salbutamol have found less clinical effectiveness and resulted in longer hospital stays. Combination therapy of saline and nebulization has more effective clinical results than single therapy of saline or nebulized drugs.